Global Distribution of the Solar Wind Flux and Velocity From SOHO/SWAN During SC‐23 and SC‐24. Issue 8 (23rd April 2019) - Koutroumpa, D.; Quémerais, E.; Ferron, S.; Schmidt, W.
Abstract: We analyze SOHO (SOlar Heliospheric Observatory)/SWAN (Solar Wind ANisotropy) hydrogen Lyman‐ α data collected between 1996 and 2018 to derive the solar wind latitudinal distribution over time. Full‐sky interplanetary Lyman‐ α maps are inverted to derive the total hydrogen ionization rate latitude profiles, normalized to proton charge‐exchange and photoionization. Using Interplanetary Scintillation velocities to calculate the velocity‐dependent charge‐exchange cross‐sections, we produce the solar wind flux latitudinal profiles. Finally, we compute solar wind velocity latitude profiles, based on the dynamic pressure and energy flux conservation (calculated from OMNI data) over latitude. SWAN reproduces the Interplanetary Scintillation velocity profiles up to at least ±60°, and also agrees with Ulysses in situ measurements for solar minimum periods in 1996–1997 and 2007. During solar maximum, discrepancies are more frequent because in situ data reflect local solar wind conditions, while SWAN data reflect global conditions in the heliosphere. Key Points: The SOHO/SWAN instrument is one of the few to derive the global solar wind distribution outside the ecliptic The data analysis produces latitude distributions for the solar wind particle flux and velocity as a function of time Comparison with IPS and Ulysses velocity data confirms the conservation of dynamic pressure and energy flux in the solar wind